2023
DOI: 10.2174/1574888x17666220422093103
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Treatment of Intervertebral Disc Degeneration: Mesenchymal Stem Cell Exosome Transplantation

Abstract: A common surgical disease, intervertebral disc degeneration (IVDD) is gradually appearing increasingly often in younger individuals. Repairing damaged intervertebral discs (IVDs) and promoting IVD tissue regeneration at the molecular level are important research goals. Exosomes are extracellular vesicles (EVs) secreted by cells and can be derived from most body fluids. Mesenchymal stem cell-derived exosomes (MSC-exos) have characteristics similar to those of the parental MSCs. These EVs can shuttle various mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…ADSC-Ex has several advantages over ADSCs themselves, including lower immunogenicity, reduced risk of tumorigenesis, and easier storage and transportation [ 26 ]. Moreover, ADSC-Ex can cross biological barriers, such as the blood-brain barrier, and target specific tissues or cells, making them an attractive therapeutic option [ 27 ] Several studies have investigated the therapeutic potential of ADSC-Ex in tissue injury models, such as myocardial infarction, acute kidney injury, and spinal cord injury [ 28 ]. These studies have shown that ADSC-Ex can promote tissue repair, reduce inflammation, and improve functional recovery [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADSC-Ex has several advantages over ADSCs themselves, including lower immunogenicity, reduced risk of tumorigenesis, and easier storage and transportation [ 26 ]. Moreover, ADSC-Ex can cross biological barriers, such as the blood-brain barrier, and target specific tissues or cells, making them an attractive therapeutic option [ 27 ] Several studies have investigated the therapeutic potential of ADSC-Ex in tissue injury models, such as myocardial infarction, acute kidney injury, and spinal cord injury [ 28 ]. These studies have shown that ADSC-Ex can promote tissue repair, reduce inflammation, and improve functional recovery [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell therapy acts as a seed by secreting cytokines and growth factors that promote the regeneration of AF [ [27] , [28] , [29] ]. Among the types of stem cells used for AF repair and regeneration, bone marrow-derived MSCs are the most commonly used stem cells [ 30 , 31 ]. However, how to promote the targeted differentiation of MSCs into AF cells has been a difficult problem.…”
Section: Discussionmentioning
confidence: 99%
“…This mode of transport plays a significant role in modulating cell behavior and highlights the complex communication that occurs between stem cells and the microenvironment of the IVD. These nuances underscore that the challenges of MSC therapy begin even at the molecular level, emphasizing the ongoing need for further investigation and innovative approaches to fully realize their potential [ 16 , 17 , 50 ]. The development of ex vivo IVD organ models is ongoing.…”
Section: Future and Dilemmasmentioning
confidence: 99%
“…One area of focus is the development of novel scaffolds or biomaterials that create a favorable environment for stem cells, thereby promoting their survival and guiding their differentiation [13,14]. Researchers are exploring different delivery methods to improve targeted delivery to specific tissues [15][16][17]. Moreover, ongoing studies are investigating the possibility of combining stem cell implantation with other therapeutic approaches, such as gene therapy or immunomodulation [4,18].…”
Section: Introductionmentioning
confidence: 99%